Small states and the strategic utility of cyber capabilities - Domingo, Francis Rico (2018)
The information revolution has profoundly influenced the interaction between states in the twenty-first century. Networked computers have supported the operations of the global financial system, industrial services, and even the conduct of military operations. Due to this revolution, the level of dependence on networked technologies has risen exponentially following the evolution of the Internet. However, networked technologies have also exposed vulnerabilities that have been exploited by hostile actors to disrupt systems, infiltrate networks, and aggravate conflicts.